EFFECTS OF PRENATAL YOGA ON MATERNAL ANXIETY - Vistra Veftisia; Luvi Dian Afriyani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Anxious or depression during pregnancy could harm both the mother and the fetus. Antidepressants did not become beneficial for pregnancy. There were several unconventional treatments for anxiety and depression in pregnancy, one of them was prenatal yoga. Prenatal yoga helps improve mood, but pregnant women do not widely use this technique. This study aimed to determine prenatal yoga's effect on pregnant women's anxiety and depression at Midwife Private Practice